Behavior of two bean varieties under two different soil water availability conditions. I. Water uptake and evapotranspiration - Vieira, Hamilton Justino; Libardi, Paulo Leonel; Bergamaschi, Homero; Angelocci, Luiz Roberto (Pesquisa Agropecuaria Brasileira, 2014)
This study aimed at testing different responses of two bean varieties (Phaseolus vulgaris L.). Aroana 80 and Aeté 3, in relation to water uptake and actual evapotranspiration over a period of soil water deficit. The trial was conducted at the Escola Superior de Agricultura "Luiz de Queiroz" (ESALQ/USP), Brazil, at a 22º70'S latitude, 47º63'W longitude and at an altitude of 586 M. Three different sowing times (15 day interval) were used. When plants of the first sowing time were at the initiation of grain formation stage, the second at the initiation of pod formation stage and the third at the initiation of bud formation stage, spray irrigation was interrupted for 17 days, in one of the replicates. During all crop cycle, water uptake by plants and water matric potential at 5011 depths of 15, 30, 45, 60 and 75 cm were measured daily by tensiometers. Available soil water fractions were also calculated. The water consumption for the variety Aroana 80 ranged from 2869 mm to 320.8 mm and from 341.7 mm 104672 mm for the treatments with and without irrigation interruption, respectively. For flue Aeté 3 variety, the water consumption ranged from 2913 mm to 307.1 mm with irrigation interruption. Available soil water fraction values were approximately 0.40, during nonirrigation period. With irrigation these values ranged from 0.52 to 0.60.